The contribution of irrigation agriculture to food security in drought prone areas: the case of Chikomba district, Zimbabwe. - Chitani, Anesu (Midlands State University, 2018)
This study seeks to evaluate the contribution of irrigation farming to food security in Zimbabwe with particular attention to Chikomba district. A mixed methodology that includes both qualitative and quantitative methods was used in the collection of data. Questionnaires, interviews and direct field observations were used as data collection tools. This study identified the crops grown in the irrigation schemes, it also determines the level of productivity and an evaluation on the contribution of the irrigation to household food security was done. Income enhancement, employment, improved health status, nutritious foods and diversity of foods from the irrigation schemes were recorded as benefits of using irrigation agriculture. Factors such as higher cost, lake of capital, lack of knowledge and skills and restrictive institutions were identified as constraints of irrigation development. The research recommends that stakeholders involved in the implementation of irrigation schemes such as ZINWA, RDC and AGRITEX should continue to work with the farmers providing them with information and knowledge about irrigation agriculture so as to improve the practice in the area. Other stakeholders and the financial institutions should be involved to enhance the productivity of the schemes so that benefits are not only limited to household food security but also include creation of employment and boosting the economy.